Mixed Aggregates of the Dilithiated Koga Tetraamine: NMR Spectroscopic and Computational Studies. (20th July 2016) - Ma, Yun; Mack, Kyle A.; Liang, Jun; Keresztes, Ivan; Collum, David B.; Zakarian, Armen
Abstract: A combination of 1 H, 6 Li, 13 C, and 15 N NMR spectroscopies and density functional theory computations explores the formation of mixed aggregates by a dilithium salt of a C2 ‐symmetric chiral tetraamine (Koga's base). Lithium halides, acetylides, alkoxides, and monoalkylamides form isostructural trilithiated mixed aggregates with few exceptions. 6 Li– 13 C and 6 Li– 15 N couplings reveal heretofore undetected transannular contacts (laddering) with lithium acetylides and lithium monoalkylamides. Marked temperature‐dependent 15 N chemical shifts seem to be associated with this laddering. Computational studies shed light on the general structures of the aggregates, their penchant for laddering, and the stereochemical consequences of aggregation.